2020
DOI: 10.1021/acs.iecr.0c04025
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Model for Oil Transport Behavior in Nanopores: Interactions between Oil and Pore Surface

Abstract: A clear knowledge of fluid flow at the nanoscale will greatly contribute to recovery of unconventional oil/gas reservoirs. The distinction of nanoconfined fluid flow behavior with that of the bulk phase stems from strong fluid–surface interactions, which favor the emergence of slip phenomenon as well as spatial variation of viscosity and further affects transport capacity. However, elaboration of the above essential relationship remains challenging nowadays. Oil possesses a complex molecular structure and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 82 publications
(121 reference statements)
0
15
0
Order By: Relevance
“…Therefore, the calculation of the slip length of oil migration in nanopores cannot use the theory of water migration in nanopores. 9,18 In this study, the slip length is calculated using the following empirical equations…”
Section: Model Validationmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, the calculation of the slip length of oil migration in nanopores cannot use the theory of water migration in nanopores. 9,18 In this study, the slip length is calculated using the following empirical equations…”
Section: Model Validationmentioning
confidence: 99%
“…However, studies have shown that the bulk oil viscosity is almost identical to that of unconfined oil, the near wall oil viscosity is greatly controlled by the oil-wall interaction, and the critical thickness of near wall oil/adsorbed oil can be reasonably determined as two layers of liquid molecules. ,,, Therefore, it is assumed that the viscosity of both bulk and near wall oil/adsorbed oil is fixed for simplicity . Meanwhile, considering that the oil migration in nanopores belongs to the laminar flow, the oil migration is dominated by the viscous resistance . Therefore, the oil flow in the two regions can be described by the basic continuity equation μ normalb r r ( r v b r ) = p x , .25em r [ 0 , r b ] μ normalw r r ( r v w r ) = p x , .25em r [ r b , r 0 ] where p is the fluid pressure, MPa; μ b and μ w are the viscosity of bulk oil and near wall oil/adsorbed oil, respectively, mPa·s; r represents the distance from oil molecule to centerline of nanopores, nm; v b and v w are the velocity of bulk oil and near wall oil/adsorbed oil, m/s; and x denotes the oil flow direction, m. r b and r 0 represent the radi...…”
Section: Model Constructionmentioning
confidence: 99%
See 3 more Smart Citations